Pembentukan Karakter Disiplin Peserta Didik Melalui Budaya Sekolah: Indonesia - Dian Rif'iyati Rif'iyati; Riyatun (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2020)
This study aims to reveal the process of establishing the disciplinary character of students through the school culture at SD Negeri 01 Legok kalong Karanganyar Pekalongan. This research is qualitative. Collecting data by observation, interviews, and documentation. Data analysis by reducing data, displaying data, and drawing conclusions. Validity of the data using triangulation. The results of the study concluded that the process of establishing the disciplinary character was carried out through planning, implementation, and evaluation. Planning includes the preparation of school goals, an arrangement of rules, and the development of school culture. The school culture is implemented through activities and rules for all school members. The establishment of the disciplinary character of students through school culture by using the method of habituation, exemplary, and advice and reprimands in every activity. The implementation includes habituation activities such as routine morning ceremonies, flag ceremonies, congregational prayer, shaking hands, praying together, washing hands, and other rules and regulations. Evaluation is carried out during the learning process, after learning, mid-semester, at the end of the semester with predetermined indicators and conveyed in the form of notes. To support the process of establishing the disciplinary character of students, namely by conducting joint meetings between teachers, parents, and students, providing guidance and direction to students.